Peran Bimbingan Penyuluhan Pendidikan Islam dalam Menghindari Perilaku Negatif - Fuadi, Anwar (Civiliza Publishing, Indonesia., 2023)
Increasing worship for police officers is crucial, especially if it is connected to the